Toxicidade do óleo essencial de tagetes minuta L (Asteraceae) em larvas de aedes aegypti (Diptera: Culicidae) e protocolo de alimentação em camundongos swiss calb/C - Lima, Waldemir Pereira (2010)
Tropical diseases have been a phenomenon of global concern, and among them the Dengue, because the mosquito that transmits the virus, Aedes aegypti (Diptera: Culicidae), became out of control, and new outbreaks have been discovered each day. Several means have been used in an attempt to control the insect life cycle. However, the indiscriminate use of many agents took the insect to develop some resistance to them. New perspectives are emerging as we find in nature means to control these mosquitoes. Is the case of essential oil of Tagetes minuta L. (Asteraceae) which, according to recent studies, plays an important role in the control of insects, including the Aedes aegypti. Objectives: develop a procedure for feeding female Aedes aegypti that does not cause stress in Swiss Balb/C mice, evaluate the toxicity and residual effect of essential oil of Tagetes minuta L (Asteraceae) on populations of Aedes aegypti. Methods: Swiss Balb/C mice were anesthetized arranged in the cage for feeding female mosquitoes for a period of one hour, three times a week. The essential oil was used in concentrations of 0,2 mL L-1; 0,225 mL L-1; 0,25 mL L-1; 0,275 mL L-1 and 0,3 mL L-1 starting from an initial dilution of 200mL L-1 in acetone, in one hundred third-stage larvae coming from Bauru-SP, São José do Rio Preto-SP, respectively, sensitive and resistant to temephos, and one hundred larvae of Rockefeller-USA. The tests were performed in four times, with three replicates for three consecutive days. Results: There was no pain or stress observed in mice during blood feeding by Ae aegypti. There was no difference between populations for susceptibility to Tagetes minuta L. and tests showed LC50 of 0,24; 0,25 and 0,21 mL L-1 and CL99, 9 at 0,35; 0,39 and 0,42 mL L- 1, respectively, for Rockefeller, Bauru and São José do Rio Preto. There was no residual effect of the oil. Conclusions: Sedation of Swiss Balb/C mice has provided it serve as a food source for female Aedes aegypti without pain or stress, and can be used by other researchers, since it was approved by the Ethics Committee of Animal Experiments (CEEA) of this institution. The LC50 of Tagetes minuta L. were equal, respectively, for larvae of the Rockefeller strain, Bauru, São José do Rio Preto, and the CL99, 9 were equal, respectively, for larvae of the Rockefeller strain, Bauru, São José do Rio Preto. The resistance of larvae to temephos had no effect on lethal action exerted by the essential oil of Tagetes minuta L. Tests for evaluation of a residual oil after a week of contact, had zero mortality. The essential oil of Tagetes minuta L can be used as an alternative larvicide against Aedes aegytpi, however new studies are needed in order to isolate the fraction of larvicidal oil and incorporate other ingredients to increase their stability so that the product can have the residual effect.